Social competence and emotional comprehension: How are they related in children? - Roazzi, A. (2014)
The developmental progression of emotional competence in childhood provides a robust evidence for its relation to social competence and important adjustment outcomes. This study aimed to analyze how this association is established in middle childhood. For this purpose, we tested 182 Portuguese children aged between 8 and 11 years, of 3rd and 4th grades, in public schools. Firstly, for assessing social competence we used an instrument directed to children using critical social situations within the relationships with peers in the school context - Socially in Action-Peers (SAp) (Rocha, Candeias & Lopes da Silva, 2012); children were assessed by three sources: themselves, their peers and their teacher. Secondly, we assessed children’s emotional understanding, individually, with the Test of Emotion Comprehension (Pons & Harris, 2002; Pons, Harris & Rosnay, 2004). Relations between social competence levels (in a composite score and using self, peers and teachers’ scores) and emotional comprehension components (comprehension of the recognition of emotions, based on facial expressions; external emotional causes; contribute of desire to emotion; emotions based on belief; memory influence under emotional state evaluation; possibility of emotional regulation; possibility of hiding an emotional state; having mixed emotions; contribution of morality to emotion experience) were investigated by means of two SSA (Similarity Structure Analysis) - a Multidimensional Scaling procedure and the external variable as points technique. In the first structural analysis (SSA) we will consider self, peers and teachers’ scores on Social Competence as content variables and TEC as external variable; in the second SSA we will consider TEC components as content variables and Social Competence in their different levels as external variable. The implications of these MDS procedures in order to better understand how social competence and emotional comprehension are related in children is discussed, as well as the repercussions of these findings for social competence and emotional understanding assessment and intervention in childhood is examined.